How to Help Senior High School Students Overcome English Writing Anxiety in Continuation Task Teaching - Zhang, Mengnan (Scientific Journal of Technology, 2025)
Despite the fact that the continuation task has various benefits for improving students’ language proficiency, it may also lead to writing anxiety among students. This paper begins by explaining the concepts of continuation task and English writing anxiety, and subsequently analyzes the factors that increase students’ writing anxiety from both teacher’s and students’ perspectives. To address this problem, this paper suggests three strategies: firstly, introducing mind mapping in continuation task teaching to aid students in understanding the story and constructing writing frameworks; secondly, enhancing students’ familiarity with the topic to align with their interests and experiences; and thirdly, implementing Teacher-Student Collaborative Assessment in continuation task teaching to establish a harmonious assessment atmosphere. These strategies aim to create a supportive writing environment for students, optimize the effectiveness of the continuation task teaching, and improve students’ overall language proficiency by alleviating their writing anxiety.